Updates on the Ultraviolet Emission from Asymptotic Giant Branch Stars. Issue Volume 14:Issue S343(2019) (August 2018) - Montez, Rodolfo; Ramstedt, Sofia; Kastner, Joel H.; Vlemmings, Wouter
Abstract: A comprehensive study of UV emission from asymptotic giant branch (AGB) stars with the Galaxy Evolution Explorer (GALEX) revealed that out of the 316 observed AGB stars, 57% were detected in the near-UV (NUV) bandpass and 12% were detected in the far-UV (FUV) bandpass (Montez et al. 2017). A cross-match between our sample and Gaia DR2 results in parallax estimates for 90% of the sample of AGB stars, compared to only 30% from Hipparcos. This increase allowed us to further probe trends and conclusions of our initial study. Specifically, that the detection of UV emission from AGB stars is subject to proximity and favorable lines of sight in our Galaxy. These improved results support the notion that some of the GALEX-detected UV emission is intrinsic to AGB stars, likely due to a combination of photospheric and chromospheric emission.